Experimental Study of Performance and Emissions of Fusel Oil-Diesel Blend in a Single Cylinder Diesel Engine - Awad, Omar I.; R., Mamat; Obed M., Ali; Mohd Fahmi, Othman; Abdul Adam, Abdullah (2017)
In order to reduce the dependency on fossil oil energy resources, the using of several energy resources in compression-ignition engine has been the target of attention of researchers. The major renewable alternative combustible species are methanol, biogas, ethanol, biodiesel, and hydrogen. Fusel oil is a by-product of bioethanol production during the fermentation process present one of the new alternative fuels for compression-ignition engine. The aim of this work is to experimentally investigate the effect of fusel oil–diesel blending on performance and emission in single cylinder compression ignition engines. The test achieved under 25 % engine load at five-engine speed 1200 to 2400 rpm with intervals of 300 rpm. The experimental results revealed that the engine indicted power and torque slightly decrease for F20 compared with pure diesel, and the increment was happened in fuel consumption. Although diesel fuel yields, the highest volumetric efficiency and exhaust temperature. Moreover, the results showed CO2 and CO were increased while the NOx emissions decrease with the use F20. All the negative effects that happened in power and torque was because of the water content, low heating value, low cetane number for fusel oil.